2011
DOI: 10.1105/tpc.111.089128
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Compound Leaf Development in Medicago truncatula by Fused Compound Leaf1, a Class M KNOX Gene  

Abstract: Medicago truncatula is a legume species belonging to the inverted repeat lacking clade (IRLC) with trifoliolate compound leaves. However, the regulatory mechanisms underlying development of trifoliolate leaves in legumes remain largely unknown. Here, we report isolation and characterization of fused compound leaf1 (fcl1) mutants of M. truncatula. Phenotypic analysis suggests that FCL1 plays a positive role in boundary separation and proximal-distal axis development of compound leaves. Map-based cloning indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 55 publications
(84 reference statements)
2
59
0
Order By: Relevance
“…KD1 is known to modulate boundary separation and proximal-distal axis development in leaves (Kimura et al, 2008;Magnani and Hake, 2008;Peng et al, 2011), and our previous microarray analysis suggested a role for KD1 in leaf and flower abscission (Meir et al, 2010). Manipulating expression of KD1 by silencing or overexpression affects various aspects of plant development.…”
Section: Discussionmentioning
confidence: 96%
“…KD1 is known to modulate boundary separation and proximal-distal axis development in leaves (Kimura et al, 2008;Magnani and Hake, 2008;Peng et al, 2011), and our previous microarray analysis suggested a role for KD1 in leaf and flower abscission (Meir et al, 2010). Manipulating expression of KD1 by silencing or overexpression affects various aspects of plant development.…”
Section: Discussionmentioning
confidence: 96%
“…M. truncatula elp1 mutants were isolated from FN and Tnt1 mutant collections as previously reported (19,36). Pea apu mutants were identified from the pea germplasm collections at The John Innes Centre (http://data.jic.bbsrc.ac.uk/cgi-bin/germplasm/pisum/) and the US Department of Agriculture-Agricultural Research Service Pacific West.…”
Section: Methodsmentioning
confidence: 99%
“…Jemalong A20. The ELP1 locus was mapped by bulked segregant analysis (BSA) and fine genetic mapping following procedures as previously reported (19,36). For BSA, two bulked pools from 50 F2 mutant plants each were analyzed using 93 SSR markers distributed on the eight chromosomes (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,No. 6 numbers and often fused leaflets [64,65]. FCL1 has targets similar to those of class 1 KNOX and is likely to work to extend the organogenic potential in dissected leaves.…”
Section: Reviewmentioning
confidence: 99%